PENGARUH PEMBERIAN KOMBINASI PUPUK KANDANG AYAM DENGAN PUPUK NPKTERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS(Zea mays. L var saccharata Sturt) - Suprianto, Amran '; ', Armaini '; Yoseva, Sri ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sweet corn widely used because it contains nutrients and high sugar content reralif. To produce high-yielding sweet corn and good quality, should consider the availability of nutrients in the soil. One effort to do that is by giving organic and inorganic fertilizers. One that includes organic fertilizer is chicken manure. While that includes inorganic fertilizer NPK compound fertilizer. The study aims to determine the effect of the combination of chicken manure with NPK fertilizer on the growth and yield of sweet corn and get treatment chicken manure and NPK fertilizer that gives the best effect. This research was conducted at the experimental station of Agriculture Faculty University of Riau. This study is an experiment using a randomized block design RAK consists of 6 treatments and repeated 4 times . The treatment is a combination of chicken manure with NPK fertilizer which consist of: P1 = 10 tonnes/ha of chicken manure to 100 kg/ha of NPK , P2 = 20 tonnes/ha of chicken manure to 200 kg/ha of NPK, P3 = 10 tonnes /ha of chicken manure to 300 kg/ha NPK , P4 = 20 tonnes/ha of chicken manure to 200 kg/ha of NPK, P5 = 10 tonnes/ha of chicken manure to 300 kg/ha of NPK, P6 = 20 tonnes/ha of chicken manure to 300 kg / ha of NPK. Based on the results of this study concluded that giving treatment chicken manure 10-20 tonnes/ha and NPK fertilizer 100-200 kg/ha gives the best results on the growth and yield of sweet corn . Keywords: Sweet Corn, Chicken Manure Fertilizer NPK